A violação de Britânico (Tac. Ann. 13.17) - Rodrigues, Nuno Simões (2021)
This essay focuses on the biography of Britannicus, son of Claudius and Valeria Messalina, considering particularly the information transmitted by Tacitus in the Annales. Tacitus’ work is also the only source that realizes that Britannicus would have been sexually assaulted by Nero, his brother by adoption, brother-in-law and rival as far as power was concerned. Thus, we also intend to analyse the reference to the stuprum of the young prince and its meaning within the historiography of Tacitus.